2020
DOI: 10.47197/retos.v38i38.76755
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-activation potentiation exercises on kicking frequency, fatigue rate and jump performance in taekwondo athletes: a case study (Efectos de los ejercicios de potenciación post activación sobre la frecuencia de pateo, tasa de fatiga y saltabi

Abstract: Abstract. The aim of the present study was to establish the effects of three conditions of post-activation potentiation (PAP) exercises on kicking frequency, fatigue rate (FR) and jump performance in novice and advanced taekwondo athletes. Secondarily, to establish if the PAP strength plus plyometrics exercises produced a significantly higher increase with respect to exercises of isolated strength and plyometrics. Eight university taekwondo athletes (n=4 novices and n=4 advanced) were randomized into four (one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 12 publications
0
14
1
4
Order By: Relevance
“…In the present study, the decrease in fatigue rate indicated by the DI could confirm the effectiveness of the plyometric CA on taekwondo-specific performance. This result was not in accordance with those previously reported in taekwondo athletes [ 26 , 43 ]. The discrepancy could be related to the difference in the methodological approaches (i.e., the CA mode and the jump height used in each trial).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, the decrease in fatigue rate indicated by the DI could confirm the effectiveness of the plyometric CA on taekwondo-specific performance. This result was not in accordance with those previously reported in taekwondo athletes [ 26 , 43 ]. The discrepancy could be related to the difference in the methodological approaches (i.e., the CA mode and the jump height used in each trial).…”
Section: Discussioncontrasting
confidence: 99%
“…However, da Silva Santos et al [ 27 ] did not report improvement in kicking performance during the FSKT-10s following three sets of ten vertical jumps above 40 cm barrier even when 10 min of rest was given. In addition, Castro-Garrido et al [ 26 ] did not find significant differences in the total number of kicks during the FSKT-mult 10 min after performing three sets of ten jumps above 20 cm. This contradiction could be related to the difference in the methodological approaches from one side and to the inter-individual variation from the other side.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Taekwondo is a combat sport practised in most countries worldwide with approximately 120 million children and adults around the world. The word taekwondo means "path of the feet and hands", which characterises this modality as a full-contact free-sparring sport that uses punching and kicking movements (Wazir et al, 2019;Castro-Garrido et al, 2020).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…Therefore, assessing sEMG in combat sports should provide exceptional care in areas such as artifacts movement and signal processing. In this sense, the taekwondo Roundhouse kick is a blow that is very representative of the speed, strength and power required in combat sports (Castro-Gatrido et al, 2020). In turn, it would be interesting to analyze whether the different processing methods used to calculate the peak EMG generate changes in the result.…”
Section: Introductionmentioning
confidence: 99%